The Influence of Spiritual Aspects and Family Support on Depression Levels among Adults at the Formoza Public Health Center, Dili, Timor-Leste - Hermin Mangande; Budiman Budiman; Khrisna Wisnusakti; Gunawan Irianto; Rahmi Imelisa (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Depression is a common mental health disorder that significantly affects the quality of life of adults. Psychosocial factors, including spiritual aspects and family support, play an important role in individual coping mechanisms and psychological adaptation. In Timor-Leste, the prevalence of depression has shown a consistent increase, highlighting the need for holistic and community-based mental health approaches. Objective: This study aimed to examine the influence of spiritual aspects and family support on depression levels among adults at the Formoza Public Health Center, Dili, Timor-Leste. Methods: This study employed a quantitative cross-sectional design. A total of 35 adults diagnosed with depression were recruited using a total sampling technique. Data were collected using the Spiritual Well-Being Scale (SWBS), a family support questionnaire, and the Beck Depression Inventory-II (BDI-II). Data analysis was conducted using univariate analysis and the Chi-square test with a significance level of α = 0.05. Results: The majority of respondents had a moderate level of spirituality (62.9%), sufficient family support (57.1%), and mild depression (54.3%). Statistical analysis showed a significant association between spiritual aspects and depression levels (p = 0.001), as well as between family support and depression levels (p = 0.001). Conclusion: Spiritual aspects and family support have a significant influence on depression levels among adults. Integrating spiritual care and strengthening family involvement are recommended as part of community mental health nursing interventions to reduce depression levels.